PERAN SATUAN POLISI PAMONG PRAJA PADA PENERTIBAN REKLAME DI KOTA SURABAYA - Angelika Putri Britniantini; Ananta Prathama (Journal Publicuho, 2023)
This study aims to examine and describe the role of the Satuan Polisi Pamong Praja Kota Surabaya (SATPOL PP) in the Enforcement of Advertising in Surabaya City. The research method uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results of the research are that the role of the Surabaya City Civil Service Police Unit in controlling advertising is considered quite good, especially in implementing policies, implementing human resources, and coordinating with related agencies. However, there are still deficiencies in providing facilities and infrastructure for dismantling and coordinating with billboard owners. An active role is needed from the Government and Civil Service Police Units to improve facilities and coordination, as well as carry out more effective outreach regarding advertising regulations.